2017
DOI: 10.1016/j.jsat.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Moderators of sudden gains after sessions addressing emotion regulation among women in treatment for alcohol use

Abstract: Sudden gains (SGs) are defined as abrupt and significant improvements in mental health symptoms that occur between two psychotherapy sessions. Preliminary evidence suggests that SGs may be an important pattern of symptom reduction in the treatment of alcohol use disorder (AUD) (i.e., a steep between-session reduction in drinking or alcohol craving frequency or intensity) (Drapkin et al., 2015). The current study examined SGs within two randomized clinical trials (RCTs) testing female-specific cognitive behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Measuring MOBCs frequently throughout treatment also may help researchers more precisely identify sources of within-person change in MOBCs, including how changes in MOBCs may be linked with specific treatment experiences or behavioral antecedents of reliable improvement (Hallgren et al, 2018). For example, previous research has identified pretreatment characteristics of individuals and within-treatment session content that are associated with sudden changes in drinking, which are subsequently associated with long-term outcomes (e.g., Drapkin et al, 2015; Holzhauer et al, 2017); future research designs that include frequent administration of MOBC measures could further identify correlates of sudden, reliable changes in MOBCs using reliable change indices to further understand factors that potentially contribute to, and result from, sudden changes in MOBCs. Future research may also identify the optimal frequency of assessments (e.g., weekly, monthly) needed for detecting reliable improvement or for concluding that such improvements have become stable over time.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring MOBCs frequently throughout treatment also may help researchers more precisely identify sources of within-person change in MOBCs, including how changes in MOBCs may be linked with specific treatment experiences or behavioral antecedents of reliable improvement (Hallgren et al, 2018). For example, previous research has identified pretreatment characteristics of individuals and within-treatment session content that are associated with sudden changes in drinking, which are subsequently associated with long-term outcomes (e.g., Drapkin et al, 2015; Holzhauer et al, 2017); future research designs that include frequent administration of MOBC measures could further identify correlates of sudden, reliable changes in MOBCs using reliable change indices to further understand factors that potentially contribute to, and result from, sudden changes in MOBCs. Future research may also identify the optimal frequency of assessments (e.g., weekly, monthly) needed for detecting reliable improvement or for concluding that such improvements have become stable over time.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Holzhauer and colleagues combined a moderator analysis with testing the intensity and timing of reductions in drinking after specific outpatient treatment sessions that targeted depression and anxiety in female-specific AUD treatment. 89 Three moderators assessed at baseline—depression, anxiety, and self-efficacy to remain abstinent in negative affect situations—predicted sudden gains (i.e., a steep decrease in drinking) after Session 5 or 6, which included interventions to attenuate negative affect. The results suggest that women who enter treatment struggling with negative affect may respond well to very specific, targeted interventions for those problems.…”
Section: Aud Treatment Services For Womenmentioning
confidence: 99%
“…An increased capacity for affect regulation has also been described as a key focus in affect-focused psychodynamic psychotherapy (Frederickson et al, 2018) and furthermore seem to work as a time-varying predictor of subsequent changes in depression in the internet-based psychodynamic treatment used in this study (Mechler et al, 2020). A study of psychotherapy for women with alcohol use disorder showed that women with low confidence in their capacity to regulate emotions without using alcohol were more inclined to experience SGs after sessions targeting emotion regulation in relation to anxiety and depression (Holzhauer et al, 2017). However, to our knowledge no studies exist examining whether increases in the capacity for emotion regulation drives sudden gains in psychotherapy.…”
Section: The Role Of Emotion Regulationmentioning
confidence: 78%